Performance Of Full-Duplex One-Way And Two-Way Cooperative Relaying Networks - Arunmozhi Sinouvassane; Nagarajan G (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The wireless research requires concurrent transmission and reception in a single time/frequency channel with good spectral efficiency. The Full duplex system is the alternate for the conventional half duplex systems. An investigation on the need for a full duplex two way (FD-TWR) and one way relaying (FD-OWR) to improve the performance of outage probability and average rate employing amplify-and-forward (AF) and decode-and-forward (DF) protocol is considered. Further the relaying systems performance under the network coding schemes is taken into consideration. The outage probability and average rate of FD-TWR and FD-OWR using a physical layer network coding was performed. In contrast to “straightforward” network coding which performs arithmetic function on digital bit streams after information have been received. The result shows the DF protocol achieves better outage probability and average rate, when compared to the AF protocol. And comparing the full duplex schemes like FD-TWR and FD-OWR, it is found that the FD-TWR achieves better outage probability and average rate, when compared to the FD-OWR. The performance was extended with different loop interference among the relay antennas. The performance show that FD-TWR performs well even in spite of loop interference.